A Novel Uni-directional Flow Circular Facility Layout for Effective Social Distancing. Issue 4 (December 2022) - Pillai, Sini V.
Hospitals have a complex infrastructure with a wide range of functional units of medical services. A well-designed facility layout planning is essential for the smooth functioning as well as to provide safe and convenient services to patients at the right time. A functional layout is suggested to optimize time and resources in the process of service delivery, reducing the challenges of patients and healthcare professionals involved in patient care. This article focuses on developing a new facility functional layout that promotes convenience, comfort and economy with enhanced quality of medical care. A pathway of patient movement is effectively designed for better health outcomes, especially when there is a huge inflow of patients seeking information about the choice of healthcare facilities and subsequent medical attention. A circular hospital facility layout with unidirectional flow is proposed, which will effectively prevent face-to-face movement of incoming and outgoing patients and their bystanders, thereby preventing spread of diseases or infection and speed up the service delivery process. The authors believe that the proposed layout will substantially improve quality, service and speed of medical procedures, though the initial investment might be higher for implementing this layout. This study is of paramount importance in maintaining social distancing at hospitals as it prevents chaotic movement of patients and more specifically total avoidance of face-to-face situations between incoming and outgoing patients.